KAJIAN PELEPAH KELAPA SEBAGAI SERAT KOMPOSIT (STUDY OF COCONUT BRANCH AS COMPOSITE FIBER) - Darmanto, Seno; Sediono, Windu; Setyoko, Bambang; Murni, Murni (TEKNIK, 2007)
Research is done to analyze coconut branch fiber as car body composite. Analyzing is based onmaterial, composition, and strength of material. Research was done in laboratory. Coconut branchfiber is obtained by natural drying process and cutting to become fiber with Â±0,5 mm of length.Reinforcement and binder is determined polyester resin. Coir (coconut fiber) have 1.15 kg/m3 ofdensity, 1.15 MPa of strength dan modulus elastisitas 4 â€“ 6 GPa. And based on specimen and studyof literatures can show that increase of cellulose of natural fiber will increase modulus of elasticity.The Increasing of modulus of elasticity will be maximal with cellulose more than 60%. Color ofspecimen is transparent yellow.